What determines women empowerment in India? A capability-based approach - Sunetra Nath; Gurudas Das (Cogent Social Sciences)
The present study aims to quantify women’s empowerment by constructing an index and attempts to investigate the potential drivers that accelerate women’s degree of empowerment using a capability-based approach. In the study, 416 married women from the Barak Valley region of Assam, India, serve as the primary sample. The index was developed using Exploratory Factor Analysis (EFA) in SPSS software. EFA identifies eight domains of women empowerment in the Indian context: technological acquaintance, household decision-making, freedom of movement, economic independence, community and political participation, gender-based violence, leadership, and work-life balance. Then, linear multiple regression was performed using the index as regressand and socio-demographic and economic factors and self-reported capabilities as regressors in the STATA software. We find that besides traditional factors, spousal work status difference, spousal work regularity, parental asset ownership, the cultural orientation of the household head, membership in multiple community groups, pre-marital agency, and financial literacy play a significant role in determining women’s empowerment.